PENGARUH MODEL PEMBELAJARAN JIGSAW TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS X DI SEKOLAH - Ananda Irvan; Alwen Bentri; Syafril; Rayendra (STKIP Subang, 2025)
The low student learning outcomes in Biology subjects due to the dominant use of the lecture method shows the need for a more effective learning model. This study aims to determine the effect of the application of the jigsaw type cooperative learning model on student learning outcomes in class X SMA Negeri 1 Batipuh. The method used was quantitative with a quasi-experimental design, involving two classes, namely the experimental class (X / Phase E8) which used the jigsaw model and the control class (X / Phase E7) which used the lecture method. Samples were selected using purposive sampling technique. Data were collected through learning outcome tests and analyzed using t-test after meeting the requirements of normality and homogeneity tests. The results showed that the average value of student learning outcomes in the experimental class was higher (77.03) compared to the control class (67.81). The t-test resulted in a tcount of 2.170 and a ttable of 1.996 at a significant level of 0.05, so the tcount> ttable and H1 is accepted. This finding proves that there is a significant effect of the application of the jigsaw type cooperative learning model on student learning outcomes. Thus, this learning model is worth applying as an alternative in improving students' Biology learning outcomes at the high school level.